1995
DOI: 10.1063/1.114197
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and magnetostriction in TbFe2 compound with the addition of manganese or gallium

Abstract: In the present study magnetic and magnetostrictive properties of Tb(Fe1−xTx)2 (T=Mn, Ga) compounds were examined by magnetic measurement, Mössbauer, and x-ray study. Mössbauer study shows that the easy magnetization direction of the compounds may deviate slightly from the major axis of symmetry and the average isomer shift of the compounds decreases with increasing the x value, which was attributed to the charge transfer from 3d electrons of Mn atoms or 4p electrons of Ga atoms into the 3d band of Fe. It was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…These alloys have been poorly studied, although it has been reported that they can exhibit a pretty high magnetostriction of around 1000 ppm. 23 Thus, in the heterostructures with thin layers, the TbFe 2 cannot be crystallized because of the low Tb content in the Tb-Fe layers. Nevertheless, our experimental results indicate the presence of another potential magnetostrictive phase.…”
Section: Resultsmentioning
confidence: 99%
“…These alloys have been poorly studied, although it has been reported that they can exhibit a pretty high magnetostriction of around 1000 ppm. 23 Thus, in the heterostructures with thin layers, the TbFe 2 cannot be crystallized because of the low Tb content in the Tb-Fe layers. Nevertheless, our experimental results indicate the presence of another potential magnetostrictive phase.…”
Section: Resultsmentioning
confidence: 99%
“…For TbMn 2 , it shows a sharp PM-AFM transition at Neel temperature T N = 40 K [15], and TbFe 2 orders ferromagnetically at T C = 697 K with a Fe magnetic moment of 2.10 B [16]. Since the distance between the nearest Fe atoms in TbFe 2 (d Fe-Fe = 2.59Å) [17] is smaller than d Mn-Mn (2.70Å) [10] in TbMn 2 , the present TbMn 1.8 Fe 0.2 sample (d Mn-Mn = 2.69Å) lies much close to the critical value of d Mn-Mn = 2.66Å, below which Mn atoms would have no intrinsic magnetic moment [18]. Therefore, Fe substitution for Mn in TbMn 2 would induce a smaller 3d-3d distance and a rapid decay of the Mn magnetism.…”
Section: Resultsmentioning
confidence: 97%
“…образуют важный в практическом отношении класс магнитных материалов, демонстрирующих высокие значения как спонтанной магнитострикции, так и магнитострикции, индуцированной внешним полем в широкой области температур, включая комнатную [1][2][3][4][5][6][7][8][9][10]. Наиболее известные среди них соединения TbFe 2 и SmFe 2 со структурой фаз Лавеса с гигантской магнитострикцией в области комнатных температур +1.7 · 10 −3 и −1.5 · 10 −3 , соответственно [11][12][13][14][15][16]. Сплавы имеют близкие по абсолютной величине значения магнитострикции, которые отличаются по знаку.…”
Section: Introductionunclassified